2021
DOI: 10.1111/cas.14866
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Arecoline induces epithelial‐mesenchymal transformation and promotes metastasis of oral cancer by SAA1 expression

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…A great deal of studies have shown that the development of OSF has been intimated to chewing betel nut commodity [ 31 ]. Arecoline is the major areca nut alkaloid and has been classified as carcinogenic to humans; it is also considered the main causative factor of OSF due to chewing betel nut [ 32 , 33 ]. However, how arecoline promotes OSF progression is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…A great deal of studies have shown that the development of OSF has been intimated to chewing betel nut commodity [ 31 ]. Arecoline is the major areca nut alkaloid and has been classified as carcinogenic to humans; it is also considered the main causative factor of OSF due to chewing betel nut [ 32 , 33 ]. However, how arecoline promotes OSF progression is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Saa1 and Saa2 genes encode serum amyloid A proteins Saa1 and Saa2, both of which are acute phase proteins [70] . Saa1 and Saa2 have been associated with pancreatic, renal, lung, colorectal, ovarian, oral, gastric, and breast cancer as well glioblastoma [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] . Although the increase in Saa1 and Saa2 proteins are typically attributed to tumor-associated inflammation, studies have shown that Saa1 can regulate Akt signaling in tumor cells and siRNA knockdown of Saa1 in pancreatic cells inhibits migration/invasion and epithelial to mesenchymal transition [ 71 , 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced glycolysis and weakened tricarboxylic acid (TCA) cycle are the key factors in regulating CAF proliferation ( 18 , 19 ). Researchers found that arecoline could promote glycolysis leading to the increase of reactive oxygen species, which could inhibit the TCA cycle and mediate tumor metastasis ( 20 , 21 ). Arecoline also led to a disordered progression of cellular aerobic metabolism by destroying cytoskeletal integrity and mitochondrial function ( 22 ).…”
Section: Introductionmentioning
confidence: 99%